Consultancy Pattern among Agriculture Students at UAS, Bangalore (Karnataka) (Indian Journal of Extension Education, 2013)
A study was conducted at UAS, Bangalore (Karnataka) during 2009 to know the consultancy pattern among students for job placement. Data were collected from B.Sc (Agriculture) final year 120 students with the help of structured pre-tested interview schedule. The study revealed that majority of the students used mass media sources to a maximum extent followed by informal and formal sources. Among the mass media sources, most of the students used website followed by newspapers, television and journals. friends, parents and relatives among informal sources and university placement cell, agricultural officers and consultants among formal sources were utilized by majority of the students.